A LABORATORY CHARACTERISTICS AND PRESENTATION OF MULTI-ORGAN AFFECTION AMONG HOSPITALIZED PATIENTS WITH SARS-CoV-2 INFECTION IN PUBLIC HOSPITAL IN BITOLA - Ilkovska, Biljana; Kotevska, Bisera; Kotevska, Sanda; Kostovska, Irena; Trajkovska, Katerina Tosheska; Kanazirev, Branimir (Journal of Morphological Sciences; Vol 4 No 1 (2021): JMS, 2021)
In December 2019, a highly infectious disease, ie, pneumonia caused by the coronavirus disease SARS-CoV-2, occurred in Wuhan, China, and the World Health Organization has declared its ongoing outbreak a pandemic. The clinical laboratory plays a key role in supporting the monitoring and management of Covid 19 disease. Our study describes the laboratory characteristics of 103, Covid 19 positive patients hospitalized in the public hospital Trifun Panovski in the period April - June 2020.  Only two patients died as a result of the Covid 19. The most common laboratory abnormalities were:  elevated lactate dehydrogenase (LDH) and C-reactive protein (CRP). Leukocytosis was found in 23,3%, and leucopenia in 3% of patients with Covid 19.  Covid 19 infection can be associated with myocardial injury, heart failure, vascular inflammation, myocarditis, cardiac arrhythmias, and hypoxic encephalopathy. We found increased values of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and Î³ â€“glutamyltransferase (Î³ â€“GT) in 35 â€“ 50% of patients. We detected  affected  renal function  in 10% of our patients with Covid 19.We identified potential biomarkers of disease severity. Our results provide guidance in risk assessment, clinical monitoring and therapy decision-making processes Keywords : Covid 19, laboratory findings, multi organ failure. https://doi.org/10.55302/JMS2141013i